Different Flushing Frequency on Blood Metabolites Profile of Ewes and Their Lambs at Pre-Weaning Period - Fassah, Dilla Mareistia; Taniasari, Mila; Daeli, Fanny Rahmasari; Diapari, Didid; Astuti, Dewi Apri; Khotijah, Lilis (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
This study determined the effects of different flushing frequency on performance and blood metabolite profile of ewes and their suckling lambs at pre-weaning period. Twelve multiparous Garut ewes (2 years-old, BW 30.06 ± 6.20 kg) and 18 lambs born to experimental ewes (lambing weight 2.49 ± 0.56 kg) were used in this study. Ewes were randomly assigned into four treatment groups in a complete block design, namely: without flushing (T0: control), flushing at the beginning of mating (T1: 2 weeks before and after mating), two times flushing (T2: T1 + 4 weeks flushing at mid-gestation), and three times flushing (T3: T2 + 2 weeks flushing at before and after parturition). Three times flushing increased ((p<0.05) the crude fat intake, while different flushing frequencies did not affect (p>0.05) dry matter intake and intakes of crude protein, crude fiber, nitrogen-free extract, and total digestible nutrients of ewes at the pre-weaning period. Different flushing frequencies did not change (p>0.05) the productive performances of ewes during the pre-weaning period. Flushing application improved (p<0.05) the average daily gain of pre-weaning lambs at 14 days, but it did not affect the weaning weight of lambs. Two times flushing showed no pre-weaning mortality rate (p<0.05). Flushing application tended to decrease (p=0.08) blood plasma triglyceride of ewes at 21- days, while two times flushing frequency tended to increase blood plasma cholesterol (p=0.05) and triglyceride (p=0.08) of lambs at 21 days. In conclusion, increased flushing frequency supports ewes and their twin lamb growth performance and blood metabolite profile at the pre-weaning period